Enhancing postgraduate students’ reading skills via the pedagogy-andragogy-heutagogy (PAH) continuum training programme / Gurnam Kaur Sidhu, Du Ruofei and Sofwah Md Nawi - Sidhu, Gurnam Kaur; Ruofei, Du; Md Nawi, Sofwah (Universiti Teknologi MARA, 2023)
Reading is often viewed as the foundation of all learning including postgraduate study. It is common for most institutions of higher learning to assume that postgraduate students come equipped with the basic competencies of literacy and the required academic reading skills. Nevertheless, studies have shown that some international students for whom English is a foreign language (EFL) face several challenges in academic reading skills. This study examined how the academic reading skills of a group of postgraduate students can be enhanced through a six-month treatment program referred to as the PAH (Pedagogy-Andragogy-Heutagogy) Continuum which emphasized a methodology that shifted from full dependence to negotiated learning and independence. The study employed a quasi-experimental research design and involved an intact group of 50 postgraduate students studying in a private university in Malaysia, where English is the medium of instruction. Data were collected through pre and post reading comprehension tests, questionnaires and five focus group interviews. Quantitative data were analysed using descriptive and inferential statistics, whilst qualitative data were analysed using thematic analysis. The findings showed that the six-month PAH-Continuum Training Programme enhanced the learners’ academic reading skills and gave them the confidence to do well in their postgraduate studies. The findings also implied that the PAH-Continuum Training programme can be utilized as a viable teaching and learning framework to help adult mature postgraduate learners develop basic competencies in postgraduate study.